Microwave-assisted delivery of an anticancer drug to cancer cells. Issue 55 (7th September 2018) - Mazinani, Sina Atrin; Stuart, Jeffrey A.; Yan, Hongbin
Abstract : Exposure of MCF-7 breast and PC-3 prostate cancer cells to 10 W microwaves at 2.45 GHz increased their uptake of doxorubicin from media by almost 100%, concomitantly increasing cell death, while microwave exposure alone had no cellular toxicity. Abstract : Exposure of MCF-7 breast and PC-3 prostate cancer cells to 10 W microwaves at 2.45 GHz increased their uptake of the cancer drug doxorubicin from media by almost 100%, concomitantly increasing cell death, while microwave exposure alone had no cellular toxicity. Addition of inhibitors of endocytosis during the treatment of MCF-7 cells with doxorubicin and microwaves showed no impact on the uptake of the anticancer drug. Furthermore, the uptake of oligonucleotides by MCF-7 cells is not affected by the treatment with microwaves. These observations suggest that endocytosis is not involved in the uptake of doxorubicin while cells are exposed to microwave irradiation. Thus, targeted low power microwave irradiation could be a safe and effective means of promoting chemotoxin delivery to cancer cells, potentially reducing the dosages and side effects of anti-cancer drugs.